Indicadores zootécnicos e econômicos da tilapicultura em tanques-rede de diferentes dimensões - de Novaes, Alex Frederico; Pereira, Gener Tadeu [UNESP]; Espagnoli Geraldo Martins, Maria Inez [UNESP] (Inst Pesca, 2012)
The present study aimed to compare the main zootechnical and economic indicators of farming tilapia in superintensive system developed in two different net cages dimensions: 6 and 18 m(3). Were used 12,960 juveniles male reversed Nile tilapia (Oreochromis niloticus), strain supreme, with an initial average weight of 32.0 g (+/- 0.85) for 6 m(3) net cages and 88.5 g (+/- 0.96) for 18 m(3) net cages. The fish were fed three times a day with commercial extruded ration, crude protein levels from 40 to 32%, particle size from 2 to 8 mm and daily feeding rate starting with 8% of live weight (LW), decreasing up to 1% LW. It was conclued that, although no statistical difference in most indicators zootechnical (P>0.05), the production of tilapias in bigger net cages resulted in lower average total cost and higher rentability per kg of fish produced, 34.4% higher, resulting in better profitability.
Zootechnical and economic indicators of the tilapia culture in net cages of different sizes
Keywords: Farming tilapia; profitability; zootechnical indicators